The Lindi Formation (upper Albian-Coniacian) and Tanzania Drilling Project Sites 36-40 (Lower Cretaceous to Paleogene): Lithostratigraphy, biostratigraphy and chemostratigraphy - Jimenez Berrocoso, A; Huber, BT; MacLeod, KG; Petrizzo, MR; Lees, JA; Wendler, I; Coxall, H; Mweneinda, AK; Falzoni, F; Birch, H; Haynes, SJ; Bown, PR; et al. (2015)
The 2009 Tanzania Drilling Project (TDP) expedition to southeastern Tanzania cored a total of 572.3 m of sediments at six new mid-Cretaceous to mid-Paleocene boreholes (TDP Sites 36, 37, 38, 39, 40A, 40B). Added to the sites drilled in 2007 and 2008, the new boreholes confirm the common excellent preservation of planktonic and benthic foraminifera and calcareous nannofossils from core samples that will be used for biostratigraphy, evolutionary studies, paleoceanography and climatic reconstructions from the Tanzanian margin, with implications elsewhere. The new sites verify the presence of a relatively expanded Upper Cretaceous succession in the region that has allowed a new stratigraphic unit, named here as the Lindi Formation (Fm), to be formally defined. The Lindi Fm (upper Albian to Coniacian), extending ∼120 km between Kilwa and Lindi, comprises a 335-m-thick, outer-shelf to upper-slope unit, consisting of dark gray claystone and siltstone interbeds, common finely-laminated intervals, minor cm-thick sandstones and up to 2.6% organic carbon in the Turonian. A subsurface, composite stratotype section is proposed for the Lindi Fm, with a gradational top boundary with the overlying Nangurukuru Fm (Santonian to Maastrichtian) and a sharp bottom contact with underlying upper Albian sandstones. The section cored at TDP Sites 36 and 38 belongs to the Lindi Fm and are of lower to middle Turonian age (planktonic foraminifera Whiteinella archaeocretacea to Helvetoglobotruncana helvetica Zones and nannofossils subzones UC6b ± UC7). The lower portion of TDP Site 39 (uppermost part of the Lindi Fm) is assigned to the lower to upper Coniacian (planktonic foraminifera Dicarinella concavata Zone and nannofossils zone UC 10), while the remaining part of this site is attributed to the Coniacian–Santonian transition and younger Santonian (planktonic foraminifera D. asymetrica Zone and upper part of nannofossils zone UC10). TDP Site 37 recovered relatively expanded (150 m thick), monotonous calcareous claystones from the lower ...